The picky eagle how democracy and xenophobia limited U.S. territorial expansion - Maass, Richard W. (2020)
"This book explains why the United States stopped annexing territory by focusing on annexation's domestic political and normative consequences"-- Provided by publisher
Keywords: Democracy -- United States -- History.; Xenophobia -- Political aspects -- United States -- History.; United States -- Territorial expansion -- History.; United States -- Foreign relations.; Xénophobie -- Aspect politique -- États-Unis -- Histoire.; États-Unis -- Expansion territoriale -- Histoire.; États-Unis -- Relations extérieures.; HISTORY -- United States -- Revolutionary Period (1775-1800); Democracy; Diplomatic relations; Territorial expansion; United States; International Relations, Diplomatic History, US History, US Foreign Policy, International Security.; Electronic books; History